ANALISIS DESKRIPTIF MOTIVASI INTERNAL DAN EKSTERNAL DOSEN DALAM MEMENUHI KINERJA TRI DHARMA PERGURUAN TINGGI - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Lecturers are professions in higher education that have complex performance criteria. The demand is not only smart, but also creative, so that it can produce quality graduates and encourage changes in people's lives for the better. However, the quality of the lecturer's performance is strongly influenced by the motivating factors. Therefore, this study was conducted to describe what factors motivate lecturers to fulfill their performance. This research was conducted on 433 lecturers of the Management Study Program at Pamulang University. However, not all lecturers were used as respondents, based on the calculation of the Slovin formula, only 81 lecturers were used as research samples. Data was collected by distributing questionnaires. This research is included in the descriptive quantitative category, where respondents' answers were analyzed descriptively based on the category of questions/statements. The results of the study explain that motivation is very important in carrying out tasks and fulfilling performance. The most dominant self-motivation is personality, while the most dominant external motivation is compensation.